Sunshine on KOLs: assessment of the nature, extent and evolution of financial ties between the leaders of professional medical associations and the pharmaceutical industry in France from 2014 to 2019: a retrospective study. Issue 2 (2nd February 2022) - Clinckemaillie, Marie; Scanff, Alexandre; Naudet, Florian; Barbaroux, Adriaan
Abstract : Objective: To investigate the financial relationships between key opinion leader (KOL) or non-KOL physicians and pharmaceutical and device companies in France. Design: Retrospective and descriptive study. Setting: All doctors practising in France, with a focus on 548 KOLs (board members of the professional medical associations that published guidelines in 2018–2019, identified on the associations' websites between 2018 and 2020). Ties were collected from the 'Transparency in Healthcare' database. Main outcome measures: The number and the value of gifts from 2014 to 2019, and of remunerations and contractual agreements from 2017 to 2019. Results: KOLs represented 0.24% of the total number of physicians in France. The total value of gifts declared in the French database for all physicians amounted to €818M (US$936M, £741M). At least one gift was declared for 83% of KOLs. KOLs' gifts represented 0.68% of the total number of gifts to physicians and 1.5% of the total value of gifts, with a mean of €3700 per capita per year. The total value of contractual agreements declared for all physicians amounted to €125M. Contractual agreements involving the KOLs represented 0.72% of the number of contractual agreements with physicians and 2.5% of the value of the agreements, with a mean of €1900 per capita per year. A total of €156M in remunerations were declared for all physicians. KOL remunerations represented 2.3% of the number of physician remunerations and 4.4% of the total value of the remunerations paid to physicians, with a mean of €4100 per capita per year. Almost all professional medical associations (99%) had at least one KOL in their board with a financial tie to the industry, but the amount varied widely among the associations. Conclusion: Financial relationships between KOLs and the industry in France are extensive. KOLs have much more financial ties than non-KOL practitioners.